A holographic telementoring system depicting surgical instrument movements for real-time guidance in open surgeries - Malek Anabtawi (19757100) (2024)
Background and Objective During open surgeries, telementoring serves as a valuable tool for transferring surgical knowledge from a specialist surgeon (mentor) to an operating surgeon (mentee). Depicting the intended movements of the surgical instruments over the operative field improves the understanding of the required tool-tissue interaction. The objective of this work is to develop a telementoring system tailored for open surgeries, enabling the mentor to remotely demonstrate the necessary motions of surgical instruments to the mentee. Methods A remote telementoring system for open surgery was implemented. The system generates visual cues in the form of virtual surgical instrument motion augmented onto the live view of the operative field. These cues can be rendered on both conventional screens in the operating room and as dynamic holograms on a head mounted display device worn by the mentee. The technical performance of the system was evaluated, where the operating room and remote location were geographically separated and connected via the Internet. Additionally, user studies were conducted to assess the effectiveness of the system as a mentoring tool. Results The system took 307 ± 12 ms to transmit an operative field view of 1920 × 1080 resolution, along with depth information spanning 36 cm, from the operating room to the remote location. Conversely, it took 145 ± 14 ms to receive the motion of virtual surgical instruments from the remote location back to the operating room. Furthermore, the user studies demonstrated: (a) mentor's capability to annotate the operative field with an accuracy of 3.92 ± 2.1 mm, (b) mentee's ability to comprehend and replicate the motion of surgical instruments in real-time with an average deviation of 12.8 ± 3 mm, (c) efficacy of the rendered dynamic holograms in conveying information intended for surgical instrument motion. Conclusions The study demonstrates the feasibility of transmitting information over the Internet from the mentor to the mentee in the form of virtual surgical instruments’ motion and projecting it as holograms onto the live view of the operative field. This holds potential to enhance real-time collaborative capabilities between the mentor and the mentee during an open surgery. Other Information Published in: Computer Methods and Programs in Biomedicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cmpb.2024.108396